Quantum sensing based on nitrogen vacancy centers in diamond and boron vacancy centers in hexagonal boron nitride - Lyu, Xiaodan (Nanyang Technological University, 2023)
Solid-state spins provide a promising platform for quantum sensing. Hexagonal boron nitride (h-BN) is not only a promising functional material for the development of 2-dimensional (2D) optoelectronic devices but also a good candidate for quantum sensing thanks to the presence of quantum emitters in the form of atom-like defects. Their exploitation in quantum technologies necessitates understanding their coherence properties as well as their sensitivity to external stimuli. In this work, we probe the strain configuration of boron vacancy centers (VB−) created by ion implantation in h-BN flakes thanks to wide field spatially-resolved optically detected magnetic resonance and sub-micro Raman spectroscopy. Our experiments demonstrate the ability of VB− for quantum sensing of strain and, given the omnipresence of h-BN in 2D-based devices, open the door for in-situ imaging of strain under working conditions. To further investigate the symmetry of h-BN, we probe the nonlinear response of h-BN flakes on the gold film, where the giant enhancement is observed. We demonstrate that the enhancement is parity independent, inspiring the nonlinear optical properties investigation for those flakes with even layers. We also verified that this enhancement is layer-dependent, which implies the change of distribution of the electric field on the surface of the film. The enhancement is broadband which means that the nonlinear optical devices can be applied for different wavelengths. We also observed an extra enhancement on the h-BN homostructures, demonstrating the probability of realizing nonlinear devices with complicated structures. This study paves the way to the ultra-elaborate definition of lattice orientation of h-BN flakes with various thicknesses, giving the possibility of strain or electric field sensing with well-defined directions of fields applied. Studies on Nitrogen-Vacancy (NV) color centers have been continued for several decades using a variety of spectroscopic techniques. The most recent renewed interest in the NV center is to explore it as a solid-state physical system for quantum sensing. Current technologies suffer from lacking high-spatial-resolution information on the target in the sample. Our proposed wide-field nuclear magnetic resonance (NMR) microscopy provides a promising solution to address the drawbacks of current technologies. By performing the dynamical decoupling and correlations measurements, we observe the time evolution of 13C in the vicinity of nitrogen-vacancy centers. The sensitivity of the wide-field microscopy is proved to reach √50nT/ Hz, which reaches the highest sensitivity reported. Last, we demonstrate the impact of 13C on the iQdyne measurement, providing a new strategy to detect nuclear spin dynamics. A more robust, rapid, and high throughput screening with high accuracy and high throughput is led by the development of the wide-field NMR system. Our study opens the door for its future usage as biosensors for disease diagnosis.